Influence of Seroreactivity to Leptospira and Reproductive Failures in Recipient Mares of Equine Embryo Transfer Programmes. Issue 4 (13th April 2013) - Pinna, A; Martins, G; Souza, G; Lilenbaum, W
Contents: The aim of this study was to demonstrate that seroreactivity against Leptospira is significantly associated to the reproductive efficiency of recipient mares of an embryo transfer (ET) programme. A serosurvey was conducted from August 2007 to March 2009 in five herds from Rio de Janeiro, Brazil, with high rates of reproductive failure, as early embryonic death (>12%), abortion (>12%) and perinatal death. Detailed information about the losses was obtained from practitioner. A total of 338 recipient mares were tested by microscopic agglutination test, and 226 (66.9%) were seroreactive, mainly against serovars Bratislava and Copenhageni. Seroreactivity could be associated to reproductive failure (p < 0.001), and it was demonstrated that a seroreactive mare is 1.8 times more likely (relative risk – RR) to present reproductive failure than a seronegative one, particularly in relation to early embryonic death (p < 0.0001; RR 8.4) but also to abortions (p < 0.0001; RR 3.5), and to perinatal death (p < 0.05; RR 7.3). Therefore, seroreactivity to Leptospira is associated to reproductive failure in all phases of pregnancy in recipient mares, impairing equine ET programmes.